A Method to Predict Rock Fracture with Infrared Thermography Based on Heat Diffusion Analysis. (28th February 2021) - Deng, Nai-Fu; Qiao, Lan; Li, Qing-wen; Hao, Jia-Wang; Wu, Shan
Abstract : The forming of micro or mesocracks on rock surfaces is a symptom and precursor of the degradation of deep surrounding rocks under excavation. However, the direct detection or observation of these tiny developed cracks is not practical due to the limitation of current instruments which can only capture and recognize macrocracks. Therefore, many indirect detection ways are proposed to acquire some precautional signals and hereby forestall damage and failure of surrounding rocks. Infrared radiation (IRR) monitoring is one of the frequently used technologies. Current thermography derived from IRR can capture all temperature changes including the surrounding environment; this may influence the on-site judgement due to uncertainty or blur of generated temperature images. This paper proposes the "pseudothermography" under the true triaxial compressive test by combining the infrared radiation data and the heat diffusion theory. Our method evenly selects 25 small regions on the observed rock surface and uses the data obtained from these regions to derive the global temperature field which contains no uncertainty. By comparing our method with the real temperature field, the deduced diffusion model proposed in this paper can relatively reflect the real crack initiation under increasing loading. The experiment result proves that the attempt for the application of heat diffusion law is feasible to indirectly reflect the formation of micro and mesocracks and, ultimately, foresee the failure of the surrounding rock.